Reflejos primitivos en el desarrollo de la motricidad gruesa de los niños y niñas de inicial I paralelo “B”, de la unidad educativa totoras de la comunidad la totora, parroquia Achupallas, cantón Alausi, provincia de Chimborazo en el periodo 2017-2018 - Mullo Mullo, Segundo Pablo (2018)
The research is intended to determine, how primitive reflexes should be stimulated from early ages since most of them have not been fully developed and as a consequence of this it affects gross motor skills at older ages. The methodology was based on a non-experimental design since none of the dependent and independent variables were manipulated, where the facts were observed. It is a documentary style for the research process that will be based on the different texts, documents and websites in order to carry out this work. The type of research correspond to a descriptive, exploratory, field and bibliographic process, since it is considered as the first scientific approach to a problem and it is used when it has not yet been addressed or has not been sufficiently studied and the existing conditions are not yet determining, when we refer to the field research, is because it was carried out in the place of the facts, and it is bibliographic, because the information was taken from several sources or bibliographical references, books and results of other researches takes, as reference the information corresponding to the variables, its population and sample were applied to 15 children of initial I parallel "B", from Totoras Educational Unit, Achupallas parish, Alausí canton, Chimborazo province, in the academic period 2017-2018